Diffusion Tensor Imaging Technology to Quantitatively Assess Abnormal Changes in Patients With Thyroid-Associated Ophthalmopathy - Rui, Li; Jing, Li; Zhenchang, Wang (Frontiers in Human Neuroscience, 2022)
Objective：We aim to investigate the feasibility of using diffusion tensor imaging (DTI）to evaluate changes in extraocular muscles (EOMs) and lacrimal gland (LG) in patients with thyroid-associated ophthalmopathy (TAO) and to evaluate disease severity. Materials and Methods: A total of 74 participants, including 17 healthy controls (HCs), 22 patients with mild TAO, and 35 patients with moderate-severe TAO, underwent 3-Tesla DTI to measure fractional anisotropy (FA) and mean diffusivity (MD) of the EOMs and LG. Ophthalmological examinations, including visual acuity, exophthalmos, intraocular pressure, and fundoscopy, were performed. FA and MD values were compared among patients with different disease severity. Multiple linear regression was adopted to predict the impact of clinical variables on DTI parameters of orbital soft tissue. Results：TAO patients’ EOMs and LG showed significantly lower FA values and higher MD compared to HCs’ (P＜0.05). Moderate-severe TAO patients’ EOMs and LG had dramatically lower FA and higher MD compared with HCs (P＜0.05). In addition, only the DTI parameters of the medial rectus were considerably different between mild and moderate-severe TAO patients (P=0.017, P=0.021). Multiple linear regression showed that disease severity had a significant impact on the DTI parameters of orbital soft tissue. Conclusion：DTI is a useful tool for detecting microstructural changes in TAO patients’ orbital soft tissue. DTI findings, especially medial rectus DTI parameters, can help to indicate the disease severity in TAO patients.